Pertumbuhan Biji Kacang Hijau Terhadap Tempat Terang Dan Gelap - Aprizal Aprizal; Arniwati Arniwati; Diana Tantia; Arni Arni (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
One of the characteristics of a living creature is growth and development. Growth and development have different meanings. However, the processes of growth and development take place simultaneously and are interrelated. Sunlight is useful for photosynthesis in plants. However, another effect of sunlight is to suppress plant cell growth. This causes plants that are exposed to sunlight to be shorter than plants that grow in the dark. This event is called etiolation. The impact on plants due to etiolation is that plants cannot carry out photosynthesis. Even though the photosynthesis process aims to produce carbohydrates which play an important role in the formation of chlorophyll. Because carbohydrates are not formed, the leaves are devoid of chlorophyll so the leaves are not green, but pale yellow.